Hubungan Pengetahuan Kesehatan Gigi Dan Mulut Dengan Kejadian Karies Gigi - Hilmiy Ila Robbihi; Anang (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2022)
The purpose of this study was to determine the relationship between knowledge of oral health and the incidence of dental caries. The type of research used in this research is an analytic survey with a cross sectional approach, namely research to study the dynamics of the influence between independent variables on the dependent variable at one time. The research location is in the Department of Nursing, Poltekkes, Ministry of Health, Tasikmalaya. However, because it was still a pandemic, the research was carried out online by filling out a questionnaire on the google form. Based on the results and the previous discussion, it can be concluded that the distribution of knowledge on oral and dental health with dental caries in D III level 1 Nursing Department students in the Academic Year 2020-2021 shows a significance value of 0.031 < 0.05, which means that there is a relationship between knowledge of oral health and caries. teeth, which means the higher the DMF-T value, the lower the level of knowledge on oral health